2019
DOI: 10.1002/mbo3.942
|View full text |Cite
|
Sign up to set email alerts
|

Effects of applying inorganic fertilizer and organic manure for 35 years on the structure and diversity of ammonia‐oxidizing archaea communities in a Chinese Mollisols field

Abstract: In this study, we investigated the physicochemical properties of soil, and the diversity and structure of the soil ammonia-oxidizing archaea (AOA) community, when subjected to fertilizer treatments for over 35 years. We collected soil samples from a black soil fertilization trial in northeast China. Four treatments were tested: no fertilization (CK); manure (M); nitrogen (N), phosphorus (P), and potassium (K) chemical fertilizer (NPK); and N, P, and K plus M (MNPK). We employed 454 high-throughput pyrosequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
8
1
Order By: Relevance
“…Notably, soil acidification was not as severe as salinization in the present study, so that significantly low pH values were only observed in CMY7. The findings are inconsistent with the results of previous findings, where both long-term monoculture and over-fertilization increased soil acidification [12,31,33]. For example, in a previous study in Shouguang, Shandong province, vegetable soil pH and soil EC were significantly negatively correlated under greenhouse production [12].…”
Section: Impacts Of Long-term Cucumber Monoculture On Soil Abiotic Propertiescontrasting
confidence: 83%
See 1 more Smart Citation
“…Notably, soil acidification was not as severe as salinization in the present study, so that significantly low pH values were only observed in CMY7. The findings are inconsistent with the results of previous findings, where both long-term monoculture and over-fertilization increased soil acidification [12,31,33]. For example, in a previous study in Shouguang, Shandong province, vegetable soil pH and soil EC were significantly negatively correlated under greenhouse production [12].…”
Section: Impacts Of Long-term Cucumber Monoculture On Soil Abiotic Propertiescontrasting
confidence: 83%
“…However, we did not observe such a correlation in Wafangdian, Liaoning province. The generally minor shifts in pH could be attributed to long-term manure and compost application, since organic manure could effectively buffer soil acidification [11,29,33].…”
Section: Impacts Of Long-term Cucumber Monoculture On Soil Abiotic Propertiesmentioning
confidence: 99%
“…Diluted metagenomic mock samples were prepared, in which the total concentrations of the six amoA genes were adjusted to 10 6 , 10 5 , and 10 4 copies/ng of DNA using commercially available plasmid DNA, referred to as Mock-copy1e6, Mock-copy1e5, and Mock-copy1e4, respectively. The adjusted concentrations were compatible with those in a wide range of environments such as soil (Bahram et al, 2022;Bannert et al, 2011;Ding et al, 2020;Han et al, 2013;Marusenko et al, 2013), wastewater (Spasov et al, 2020;Wang et al, 2021;Zhang et al, 2015), estuaries (Hollibaugh et al, 2011), and seawater (Christman et al, 2011). OTUs were de novo predicted using pooled reads from three capture and three non-capture samples.…”
Section: Study Of Targeted Gene Concentration Sensitivitymentioning
confidence: 64%
“…However, the target genes typically exist at low concentrations in heterogeneous DNA samples. The concentration of amoA was estimated to be up to 10 8 copies per ng of DNA in soil (Bahram et al, 2022; Bannert et al, 2011; Ding et al, 2020; Han et al, 2013; Marusenko et al, 2013), wastewater (Spasov et al, 2020; Wang et al, 2021; Zhang et al, 2015), estuaries (Hollibaugh et al, 2011), and seawater (Christman et al, 2011) using quantitative real-time PCR (qPCR), and less than 0.001% and 0.05% of the metagenomic and metatranscriptomic reads, respectively, were assigned to the amoA gene from soil samples (Bahram et al, 2022; Clark et al, 2021; Paungfoo-Lonhienne et al, 2017). This low concentration limits the community-wide analysis of genes of interest to a realizable sequencing depth.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported contrasting results about the relative abundance and structural composition of AOA communities. Some studies demonstrated that different N fertilizer management approaches significantly impact the AOB communities over AOA ( Sun et al, 2019 ; Ding et al, 2020 ), whereas a few studies revealed that the structural composition and the relative abundance of AOA communities were significantly sensitive to different fertilizer management strategies ( Mukhtar et al, 2019 ). Amazingly, the structural composition of AOA has been noticed to depict an intensive correlation between AOA composition and soil properties and environmental conditions, which necessarily reported that a single soil or environmental parameter does not decide the structural composition of AOA in the soil ( Jiang et al, 2014 ; Zhang et al, 2019a ).…”
Section: Toward Eco-efficient N Managementmentioning
confidence: 99%